Analisis Kebutuhan Sistem Informasi Pemantauan Pekerja Migran Indonesia - Leonardi Paris Hasugian; Rangga Sidik; Yeffry Handoko Putra; Yusrila Y Kerlooza; Deden A Wahab (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
There are still many Indonesian Migrant Worker - Pekerja Migran Indonesia (PMI) involved in crime, both as victims and under the state. This shows that stakeholders including the government in the protection of PMI have not been idealized. Current efforts tend to focus on laws and regulations, on the other hand the lack of response, time, and precise. That issues should be avoided if there is a continuous form of communication between PMI and the government and / or other stakeholders during the placement of PMI abroad. This study resulted in a needs analysis to develop monitoring information system to provide information on PMI. The needs analysis results in PEST and SWOT analysis. Indicate that PMI need to make reports regularly using a monitoring information system. The monitoring information system will monitor PMI's condition to assess their situation and notify the government and / or other stakeholders if there is a response that needs to be followed up..